A Commercial Conducting Polymer as Both Binder and Conductive Additive for Silicon Nanoparticle-Based Lithium-Ion Battery Negative Electrodes - COLEMAN, JONATHAN; NICOLOSI, VALERIA; DUESBERG, GEORG; MCEVOY, NIALL (My University, 2016)
This work describes silicon nanoparticle-based lithium-ion battery negative electrodes where multiple non-active electrode additives (usually carbon black and an inert polymer binder) are replaced with a single conductive binder; in this case the conducting polymer PEDOT:PSS. While enabling the production of well-mixed slurry-cast electrodes with high silicon content (up to 95 wt%), this combination eliminates the well-known occurrence of capacity losses due to physical separation of the silicon and traditional inorganic conductive additives during repeated lithiation/delithiation processes. Using an in situ secondary doping treatment of the PEDOT:PSS with small quantities of formic acid, electrodes containing 80 wt% SiNPs can be prepared with electrical conductivity as high as 4.2 S/cm. Even at the relatively high mass loading of 1 mg/cm2, this system demonstrated a first cycle lithiation capacity of 3685 mAh/g (based on the SiNP mass) and a first cycle efficiency of ~78%. After 100 repeated cycles at 1 A/g this electrode was still able to store an impressive 1950 mAh/g normalised to Si mass (~75% capacity retention), corresponding to 1542 mAh/g when the capacity is normalized by the total electrode mass. At the maximum electrode thickness studied (~1.5 mg/cm2) a high areal capacity of 3 mAh/cm2 was achieved. Importantly, these electrodes are based on commercially available components and are produced by the standard slurry coating methods required for large-scale electrode production. Hence, the results presented here are highly relevant for the realisation of commercial LiB negative electrodes that surpass the performance of current graphite-based negative electrode systems.
PUBLISHED
Cited By :1 Export Date: 15 September 2016
Keywords: anode, battery, binder, conducting polymer, conducting additive, negative electrode, PEDOT:PSS, silicon.; anode, battery, binder, conducting polymer, conducting additive, negative electrode, PEDOT:PSS, silicon.